Statistical sampling for audit and control - McRae, T. W. (London ; New York : Wiley, 1974)
Statistical sampling is the scientific approach to auditing.By using the method the auditors improves both the accuracy and interest of his work and the image of his profession.
"A Wiley-Interscience publication."
Includes index.
Includes bibliographical references: p. 273-274.
aia 03/04/2018
Loans
Keywords: Auditing; Sampling (Statistics).; Accounting